Molten salt assisted synthesized ultrathin carbon nanosheet loaded high-entropy monatomic catalyst as well as preparation method and application of fused salt assisted synthesized ultrathin carbon nanosheet loaded high-entropy monatomic catalyst

Ultra-thin carbon nanosheets loaded with high entropy single atom catalyst was prepared through molten salt-assisted synthesis technology, which solved the problem of sulfur cathode kinetics in lithium-sulfur batteries, and achieved efficient polysulfide conversion and improved battery circulation performance.

CN119608180AActive Publication Date: 2025-03-14GUANGDONG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411451929.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-14
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The diffusion of intermediate lithium polysulfide and slow sulfur redox conversion kinetics in the sulfur cathode in the lithium sulfur battery lead to poor specific capacity, poor rate performance and rapid capacity degradation.

Method used

Ultrathin carbon nanosheets are prepared by molten salt-assisted synthesis technology, and a uniform liquid-phase nucleation environment formed by molten salt is improved, the growth barrier of 2D materials is reduced, and a two-dimensional nanoreactor with rich porous structure is formed.

Benefits of technology

It significantly improves the polysulfide adsorption conversion kinetics, inhibits the shuttle effect, improves the conductive properties of sulfur, and improves the circulation performance of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608180A_ABST
    Figure CN119608180A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrathin carbon nanosheet loaded high-entropy monatomic catalyst synthesized under assistance of molten salt as well as a preparation method and application of the ultrathin carbon nanosheet loaded high-entropy monatomic catalyst. The preparation method of the ultrathin carbon nanosheet loaded high-entropy monatomic catalyst comprises the following steps: providing ZIF-67 powder; coating with a dopamine solution, so as to obtain ZIF-67 (at) PDA powder; the obtained ZIF-67 (at) PDA powder is subjected to heat treatment, and a Co organic framework hollow dodecahedron coated with dopamine is obtained; then adding soluble metal salt and fused salt, and further pyrolyzing in a nitrogen atmosphere; and finally, carrying out acid washing and water washing to obtain the high-entropy monatomic catalyst loaded on the ultrathin carbon nanosheet. The preparation method of the ultrathin carbon nanosheet loaded high-entropy monatomic catalyst is energy-saving, adopts a molten salt process, and is mild in reaction condition; the prepared ultrathin carbon nanosheet is large in specific surface area, provides a larger reaction activity surface, and is applied to a lithium-sulfur battery, so that the lithium-sulfur battery shows excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to new chemical energy materials, and in particular to a molten salt-assisted synthesis of ultra-thin carbon nanosheet-loaded high-entropy single-atom catalyst, and a preparation method and application thereof. Background Art

[0002] Lithium-sulfur batteries are considered to be the next generation of secondary batteries because of their high theoretical capacity (S: 1675 mAh / g and Li: 3860 mAh / g), sustainability of S, and lowest reduction potential of Li (-3.04 V relative to standard hydrogen electrode). Despite decades of efforts, lithium-sulfur batteries still have some detrimental problems associated with the cathode and anode. For sulfur cathodes, the diffusion of intermediate lithium polysulfides and slow sulfur redox conversion kinetics lead to poor specific capacity, poor rate performance, and rapid capacity degradation. Therefore, it is urgent to design a kinetically advanced lithium-sulfur battery system with good structure for lithium polysulfide-inhibited cathodes. In order to solve these problems of sulfur electrodes, elemental sulfur is usually loaded (filled, attached, mixed, epitaxially grown, coated, etc.) into nanoreactor materials with high specific surface area, high porosity and good conductivity to form composite positive electrode materials to limit the dissolution of polysulfides into the electrolyte during the cycle and the various negative effects caused by it.

[0003] At present, there are various types of nanoreactors for preparing nanoparticles and nanowires (rods), such as micelles and carbon nanotubes. Nanoreactors play an important role in controlling reaction selectivity and product morphology. With the discovery of graphene, two-dimensional materials have gained widespread interest in scientific and applied research. At present, the synthesis of two-dimensional materials mainly includes the interface method and the layered crystal exfoliation method. The interface method is limited to low yield, and the layered crystal exfoliation method is limited to the very limited layered crystals that can be used for exfoliation. Therefore, the development of a new type of two-dimensional nanoreactor will open up a new method for the synthesis of two-dimensional materials. Summary of the invention

[0004] Molten salt assisted synthesis (MSAS) technology combines the advantages of traditional solid-phase and liquid-phase synthesis methods, while giving full kinetic accessibility to catalyst synthesis and controllability of nanocrystal size, morphology and size, becoming an important means of preparing catalysts. In order to further improve the adsorption and conversion kinetics of polysulfide, more types of elements are introduced into the single-atom system. The rich active sites of high-entropy single-atom catalytic materials and the synergistic effect between different active sites show excellent electrochemical performance when used in lithium-sulfur batteries.

[0005] Based on this, the purpose of the present invention is to provide a molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalysts and a preparation method thereof. The uniform liquid phase nucleation environment formed by the molten salt plays a vital role in increasing the reaction rate, reducing the growth barrier of 2D materials, and improving the yield.

[0006] A method for preparing a high-entropy single-atom catalyst supported by ultrathin carbon nanosheets assisted by molten salt synthesis comprises the following steps:

[0007] S1: Dispersing ZIF-67 powder in tris(hydroxymethylaminomethane) hydrochloride buffer solution, then coating with dopamine solution, and then drying the product by centrifugation to obtain ZIF-67@PDA powder;

[0008] S2: The obtained ZIF-67@PDA powder is subjected to a heat treatment to obtain a dopamine-coated Co organic framework hollow dodecahedron;

[0009] S3: adding a variety of soluble metal salt solutions and molten salts to the reaction system obtained in step S2, freeze-drying after ultrasonic treatment, and pyrolyzing under a nitrogen atmosphere;

[0010] S4: Wash with acid solution and deionized water to remove the salt template and aggregated metal particles to obtain a high-entropy single-atom catalyst supported on ultrathin carbon nanosheets.

[0011] The molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalyst preparation method provided by the present invention, by using molten salt as a template to assist in the pyrolysis process, the molten salt can be used as a stripping agent to embed, strip and etch the carbon material of Co-PDA, which leads to the formation of a two-dimensional, porous carbon material with a rich porous structure (defective carbon). At the same time, these defective carbons (pyridinic N and intrinsic carbon defects) can be used as anchors for capturing metal atoms. Finally, after leaching the agglomerated metal particles, a two-dimensional nanoreactor of ultra-thin carbon nanosheets loaded with high entropy single atoms is obtained.

[0012] Furthermore, in step S1, the nitrogen source in the dopamine solution includes one or more of dopamine, urea, melamine and glycine.

[0013] Furthermore, in step S1, the pH value of the tris(hydroxymethyl)aminomethane hydrochloride) buffer solution is 7-9.

[0014] Furthermore, in step S1, the mass volume ratio of the ZIF-67 powder to the tris(hydroxymethyl)aminomethane hydrochloride buffer solution is (0.1-0.2) g: (60-80) ml.

[0015] Furthermore, in step S1, the dopamine coating temperature is room temperature and the stirring time is 10 hours.

[0016] Further, in step S2, the obtained ZIF-67@PDA powder is dispersed in 20 mL of deionized water, heated to 70-100° C., and maintained for 20-50 min.

[0017] Furthermore, in step S3, the soluble metal salt solutions include five or more kinds.

[0018] Furthermore, in step S3, the metal elements in the soluble metal salt solution are selected from at least four of Fe, Ni, Ir, Pd, and Ce, and the soluble metal salt solution is selected from at least one of nitrate, chloride, acetylacetonate, and acetate.

[0019] Furthermore, the molten salt includes at least one or more of sodium chloride, calcium chloride and potassium chloride.

[0020] Furthermore, in step S3, the mass ratio of the dopamine-coated cobalt metal organic framework hollow dodecahedron to the soluble metal salt solution is 2:5.

[0021] Furthermore, the mass ratio of the soluble metal salt to the molten salt is 1:3.

[0022] Furthermore, in step S3, the temperature of the pyrolysis in the nitrogen atmosphere is 600-800°C, the time is 1-3h, and the heating rate is 1°C / min-10°C / min.

[0023] It should be noted that the purpose of the pyrolysis process in the present invention is to reach the temperature at which each key reaction occurs, and to maintain a certain time to ensure the completeness of the reaction. Pyrolysis has multiple heating processes, which are determined according to the reaction between the reactants, and the temperature and time are set to ensure the completeness of the reaction. If there is no reasonable process setting, it may lead to uneven product morphology, a large loss of raw materials, etc.

[0024] Specifically, the pyrolysis temperature in the preparation method of the present invention is 600° C.-800° C. Exemplarily, the sintering temperature of the heat treatment can be 600° C., 700° C., 800° C. or a range consisting of any two of the above values.

[0025] Specifically, the pyrolysis time in the preparation method of the present invention is 1 hour to 3 hours. Exemplarily, the sintering time of the first heat treatment can be 1 hour, 2 hours, 3 hours, or a range consisting of any two of the above values.

[0026] Specifically, the heating rate of the pyrolysis in the preparation method of the present invention is 1°C / min-10°C / min. Exemplarily, the heating rate of the first heat treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or a range consisting of any two of the above values.

[0027] By adopting the above-mentioned heat treatment conditions, the degree of completion of the reaction can be improved, which is conducive to obtaining two-dimensional nanomaterials with stable properties.

[0028] A molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalyst is prepared by the molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalyst preparation method of the present invention.

[0029] Furthermore, the thickness of the molten salt-assisted synthesis of ultra-thin carbon nanosheets is 0.4 to 1.2 nm.

[0030] Furthermore, the molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalysts includes metal elements Fe, Co, Ni, Ir, and Pd; and the atomic molar ratio of Fe, Co, Ni, Ir, and Pd is 0.8:1:0.8:0.6:0.4;

[0031] Alternatively, the molten salt-assisted synthesis of ultrathin carbon nanosheets loaded with high entropy single-atom catalysts includes metal elements Fe, Co, Ni, Ir, and Ce, and the atomic molar ratio of Fe, Co, Ni, Ir, and Ce is 0.7:1:0.6:0.6:0.4;

[0032] Alternatively, the ultra-thin carbon nanosheet-loaded high-entropy single-atom catalyst includes metal elements Fe, Co, Ni, Pd, and Ce, and the atomic molar ratio of Fe, Co, Ni, Pd, and Ce is 0.7:1:0.6:0.5:0.5.

[0033] The present invention also provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active layer arranged on at least one side of the positive electrode collector, and the positive electrode active layer includes an ultra-thin carbon nanosheet loaded with a high-entropy single-atom catalyst obtained by the preparation method described in the present invention or a modified ultra-thin carbon nanosheet loaded with a high-entropy single-atom catalyst obtained by the preparation method described in the present invention.

[0034] The present invention also provides a secondary battery, comprising the positive electrode plate as described in the present invention.

[0035] The present invention also provides the use of ultra-thin carbon nanosheets loaded with high entropy single-atom catalysts in secondary batteries, electrocatalytic materials, lithium-sulfur batteries and lithium metal batteries.

[0036] Specifically, sulfur powder and ultra-thin carbon nanosheets loaded with high entropy single atom catalyst material are weighed in a mass ratio of 7:3, mixed thoroughly, and heated to 155° C. to melt the sulfur in a reactor for 12 hours to obtain a sulfur-loaded ultra-thin carbon nanosheets loaded with high entropy single atom catalyst material positive electrode material.

[0037] The obtained ultra-thin carbon nanosheets loaded with sulfur were mixed with high entropy single-atom catalyst materials, carbon black conductive agent (SuperP) and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added, ground into a paste in an agate mortar, applied on the current collector aluminum foil, and then placed in a 60°C vacuum drying oven for 8 hours, and cut to prepare the pole piece. Then they were all transferred to a glove box filled with argon gas for assembly of button cells. The button cell model was CR2032, with a metal lithium sheet as the counter electrode, a polypropylene microporous membrane Celgard 2400 as the diaphragm, and an electrolyte of 1 mol / L LiPF6 / EC+DMC+EMC (V / V=1:1:1).

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The present invention develops a universal molten salt-assisted synthesis of two-dimensional nanoreactors. The uniform liquid nucleation environment formed by the molten salt plays a vital role in increasing the reaction rate, reducing the growth barrier of 2D materials, and increasing the yield. During the molten salt-assisted pyrolysis process, metal chlorides (e.g., NaCl) can be used as stripping agents to embed, strip, and etch the carbon materials of Co-PDA, which leads to the formation of two-dimensional, porous carbon materials with rich porous structures (defective carbon). At the same time, these defective carbons (pyridinic N and intrinsic carbon defects) can be used as anchors to capture metal atoms. Finally, after leaching the agglomerated metal particles, a two-dimensional nanoreactor loaded with high entropy single atoms of ultrathin carbon nanosheets is obtained.

[0040] 2. Molten salt can induce the formation of high-entropy single atoms and porous graphene-like carbon, which is conducive to the full exposure of active centers. At the same time, the introduction of multiple metal elements forms different coordination and geometric effects, which can effectively anchor polysulfides and accelerate their conversion, thereby effectively inhibiting the shuttle effect and improving the utilization rate of active substances.

[0041] 3. The prior art synthesizes ultra-thin carbon nanosheets loaded with high-entropy single atoms or high-entropy alloys based on modified synthesis on the basis of two-dimensional materials (carbon-nitrogen substrates). The starting point of the present invention is to directly synthesize thin carbon nanosheets loaded with high-entropy single atoms, eliminating the step of purchasing or preparing two-dimensional materials; secondly, the prior art synthesizes high-entropy single atoms or high-entropy alloys under high temperature conditions (1000°C), and the preparation method of the present invention adopts the molten salt method with a pyrolysis temperature of 600-800°C, which has relatively mild conditions and low energy consumption; the prepared two-dimensional layered nanomaterial has a regular structure and good electrocatalytic performance.

[0042] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic diagram of the preparation process of molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalysts;

[0044] Figure 2 is a SEM image of the two-dimensional layered nanosheet prepared in Example 1;

[0045] Figure 3 is a SEM image of the two-dimensional layered nanosheet prepared in Example 2;

[0046] Figure 4 is a SEM image of the two-dimensional layered nanosheet prepared in Example 3;

[0047] Figure 5 is a TEM image of the two-dimensional layered nanosheet prepared in Example 1;

[0048] Figure 6 It is a lithium-sulfur battery cycle performance diagram of the positive electrode materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] In the preparation method of the present invention, by controlling the reaction conditions, especially the pyrolysis temperature, different pyrolysis temperatures can make the pore structure of the carbon-nitrogen material different, thereby affecting its porosity and pore size distribution, thereby affecting the reaction site for polysulfide adsorption conversion. Suitable reaction sites can accelerate the kinetics of polysulfide conversion and reduce the chance of lithium polysulfide dissolving in the electrolyte, thereby further reducing the amount of lithium polysulfide dissolved in the electrolyte and further improving the cycle stability of the lithium-sulfur battery.

[0051] The present invention provides a molten salt-assisted preparation process for ultra-thin carbon nanosheets loaded with high entropy single-atom catalysts, comprising the following steps:

[0052] S1: Dispersing ZIF-67 powder in a tris(hydroxymethyl)aminomethane hydrochloride) buffer solution with a pH value of 7 to 9, and then coating with a dopamine solution at room temperature by stirring, and then drying the product by centrifugation to obtain ZIF-67@PDA powder;

[0053] S2: The obtained ZIF-67@PDA powder was added into deionized water, heated to 85 °C, and maintained for 30 min to obtain dopamine-coated Co organic framework hollow dodecahedrons;

[0054] S3: adding a variety of soluble metal salt solutions and molten salts to the reaction system obtained in step S2, freeze-drying after ultrasonic treatment, and pyrolyzing at 600-800° C. with a heating rate of 1° C. / min-10° C. / min for 1 to 3 hours under a nitrogen atmosphere;

[0055] S4: Wash with acid solution and deionized water to remove the salt template and aggregated metal particles to obtain a high-entropy single-atom catalyst supported on ultrathin carbon nanosheets.

[0056] Example 1

[0057] First, the cobalt-based metal-organic framework ZIF-67 was prepared at room temperature by coprecipitation method, and the precursor solution was prepared. Weigh 4.516g (55mmol) of 2-methylimidazole, add 60ml of water, and stir magnetically to dissolve, which is recorded as solution A; weigh 0.291g (1mmol) of cobalt nitrate hexahydrate, add 20ml of water, and stir magnetically to dissolve; weigh 5mg of hexadecyltrimethylammonium bromide (CTAB), pour it into the cobalt nitrate solution, which is recorded as solution B. Pour solution B into solution A and react at 300-400 rpm for 1h. Centrifuge after the reaction. Put the product obtained by centrifugation into an oven at 70°C for drying to obtain ZIF-67 powder. The prepared ZIF-67 powder (0.1 g) was dispersed in 70 mL of Tris-HCl buffer solution (pH = 8.5) to form a suspension, and then 20 mL of dopamine (0.1 g) solution was added dropwise to the above suspension and stirred continuously at room temperature for 10 h. The product was then obtained by centrifugation, washed 3 times in deionized water, and then dried at room temperature. The obtained ZIF-67@PDA powder was dispersed in 20 mL of deionized water, heated to 85 °C, and maintained for 30 min to obtain hollow dodecahedral Co-PDA. According to the atomic molar ratio of Fe, Co, Ni, Ir, and Pd of 0.8:1:0.8:0.6:0.4, 190 mg of ferric nitrate nonahydrate, 146 mg of nickel nitrate hexahydrate, 207 mg of iridium nitrate trihydrate, and 92 mg of palladium nitrate were weighed in a 100 mL beaker, and 70 mL of ethanol was added and stirred for 15 minutes. At this time, the total concentration of metal salts was 10 mmol / L, and then 50 mL of sodium chloride was added, ultrasonically treated for 1 h, and freeze-dried; subsequently, it was further pyrolyzed at 800 °C in a nitrogen atmosphere, and finally washed with 1 mol HCl solution and deionized water to remove the NaCl template and aggregated metal particles. After drying, two-dimensional nanosheet powder was obtained.

[0058] Sulfur powder and two-dimensional nanosheet powder were weighed in a mass ratio of 7:3, mixed thoroughly, and heated to 155° C. to melt the sulfur in a reactor for 12 hours to obtain a sulfur-loaded ultra-thin carbon nanosheet-loaded high-entropy single-atom catalyst material positive electrode material 1.

[0059] Example 2

[0060] First, the cobalt-based metal-organic framework ZIF-67 was prepared at room temperature by coprecipitation method, and the precursor solution was prepared. Weigh 4.516g (55mmol) of 2-methylimidazole, add 60ml of water, and stir magnetically to dissolve, which is recorded as solution A; weigh 0.291g (1mmol) of cobalt nitrate hexahydrate, add 20ml of water, and stir magnetically to dissolve; weigh 5mg of hexadecyltrimethylammonium bromide (CTAB), pour it into the cobalt nitrate solution, which is recorded as solution B. Pour solution B into solution A and react at 300-400 rpm for 1h. Centrifuge after the reaction. Put the product obtained by centrifugation into an oven at 70°C for drying to obtain ZIF-67 powder. The prepared ZIF-67 powder (0.1 g) was dispersed in 70 mL of Tris-HCl buffer solution (pH = 8.5) to form a suspension, and then 20 mL of dopamine (0.1 g) solution was added dropwise to the above suspension and stirred continuously at room temperature for 10 h. The product was then obtained by centrifugation, washed 3 times in deionized water, and then dried at room temperature. The obtained ZIF-67@PDA powder was dispersed in 20 mL of deionized water, heated to 85 °C, and maintained for 30 min to obtain hollow dodecahedral Co-PDA. According to the atomic molar ratio of Fe, Co, Ni, Ir, and Pd of 0.8:1:0.8:0.6:0.4, 190 mg of ferric nitrate nonahydrate, 146 mg of nickel nitrate hexahydrate, 207 mg of iridium nitrate trihydrate, and 92 mg of palladium nitrate were weighed in a 100 mL beaker, and 70 mL of ethanol was added and stirred for 15 minutes. At this time, the total concentration of metal salts was 10 mmol / L, and then 50 mL of sodium chloride was added, ultrasonically treated for 1 h, and freeze-dried; subsequently, it was further pyrolyzed at 600 °C in a nitrogen atmosphere, and finally washed with 1 mol HCl solution and deionized water to remove the NaCl template and aggregated metal particles. After drying, two-dimensional nanosheet powder was obtained.

[0061] Example 3

[0062] First, the cobalt-based metal-organic framework ZIF-67 was prepared at room temperature by coprecipitation method, and the precursor solution was prepared. Weigh 4.516g (55mmol) of 2-methylimidazole, add 60ml of water, and stir magnetically to dissolve, which is recorded as solution A; weigh 0.291g (1mmol) of cobalt nitrate hexahydrate, add 20ml of water, and stir magnetically to dissolve; weigh 5mg of hexadecyltrimethylammonium bromide (CTAB), pour it into the cobalt nitrate solution, which is recorded as solution B. Pour solution B into solution A and react at 300-400 rpm for 1h. Centrifuge after the reaction. Put the product obtained by centrifugation into an oven at 70°C for drying to obtain ZIF-67 powder. The prepared ZIF-67 powder (0.1 g) was dispersed in 70 mL of Tris-HCl buffer solution (pH = 8.5) to form a suspension, and then 20 mL of dopamine (0.1 g) solution was added dropwise to the above suspension and stirred continuously at room temperature for 10 h. The product was then obtained by centrifugation, washed 3 times in deionized water, and then dried at room temperature. The obtained ZIF-67@PDA powder was dispersed in 20 mL of deionized water, heated to 85 °C, and maintained for 30 min to obtain hollow dodecahedral Co-PDA. According to the atomic molar ratio of Fe, Co, Ni, Ir, and Pd of 0.8:1:0.8:0.6:0.4, 190 mg of ferric nitrate nonahydrate, 146 mg of nickel nitrate hexahydrate, 207 mg of iridium nitrate trihydrate, and 92 mg of palladium nitrate were weighed in a 100 mL beaker, and 70 mL of ethanol was added and stirred for 15 minutes. At this time, the total concentration of metal salts was 10 mmol / L, and then 50 mL of sodium chloride was added, ultrasonically treated for 1 h, and freeze-dried; subsequently, it was further pyrolyzed at 700 °C in a nitrogen atmosphere, and finally washed with 1 mol HCl solution and deionized water to remove the NaCl template and aggregated metal particles. After drying, two-dimensional nanosheet powder was obtained.

[0063] Comparative Example 1

[0064] CNT-S Lithium-sulfur Battery Cathode Material

[0065] Sulfur powder and carbon nanotube (CNT) material were weighed in a mass ratio of 7:3, mixed thoroughly, and heated to 155° C. to melt sulfur in a reactor for 12 hours to obtain sulfur-loaded CNT-S lithium-sulfur battery positive electrode material 4.

[0066] Performance Testing

[0067] The ultra-thin carbon nanosheets loaded with high entropy single atom catalysts prepared in Examples 1-3 and Comparative Example 1 were subjected to the following performance tests:

[0068] 1. SEM test

[0069] Figure 2-4The SEM images of the two-dimensional layered nanosheets prepared in Examples 1-3 are shown. It can be seen from the images that the products obtained by the preparation method of the present invention are all sheet-like nanomaterials. Figure 2 It can be seen that the product prepared in Example 1 is a two-dimensional layered nanosheet. Figure 3 It can be seen that the product prepared in Example 2 is a two-dimensional layered nanosheet. Compared with Example 1, the nanosheet prepared in Example 2 has more pores. Figure 4 It can be seen that the product prepared in Example 3 is a two-dimensional layered nanosheet. Compared with Example 1, Example 3 produces nanofragments.

[0070] 2. TEM test

[0071] Figure 5 This is a TEM image of the two-dimensional layered nanosheet prepared in Example 1. It can be seen from the transmission electron microscope image that the product prepared in Example 1 is a two-dimensional layered nanosheet.

[0072] 3. Battery performance test

[0073] The prepared positive electrode material, carbon black conductive agent (Super P) and polyvinylidene fluoride (PVDF) binder were mixed in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added, ground into a paste in an agate mortar, applied on the current collector aluminum foil, and then placed in a 60°C vacuum drying oven for 8 hours, and cut to prepare the pole piece. Then they were all transferred to a glove box filled with argon gas for assembly of button cells. The button cell model was CR2032, with a metal lithium sheet as the counter electrode, a polypropylene microporous membrane Celgard 2400 as the separator, and an electrolyte of 1 mol / L LiPF6 / EC+DMC+EMC (V / V=1:1:1).

[0074] Figure 6 The lithium-sulfur battery cycle performance diagram of the positive electrode materials prepared in Example 1 and Comparative Example 1. Figure 6 It can be seen that the battery performance of the positive electrode material 1 prepared in Example 1 is significantly better than that of the positive electrode material 4 prepared in Comparative Example 1 when tested at a current density of 1C. It can be seen that the ultra-thin carbon nanosheet-loaded high-entropy single-atom catalyst prepared by the preparation method of the present invention has good electrocatalytic performance. When applied to lithium-sulfur batteries, it accelerates the kinetics of polysulfide adsorption and conversion, inhibits the shuttle effect, and also improves the conductivity of sulfur, so that the lithium-sulfur battery exhibits excellent cycle performance.

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A method for preparing a high-entropy single-atom catalyst supported by ultrathin carbon nanosheets assisted by molten salt, characterized in that: The following steps are involved: S1: Dispersing ZIF-67 powder in tris(hydroxymethylaminomethane) hydrochloride buffer solution, then coating with dopamine solution, and then drying the product by centrifugation to obtain ZIF-67@PDA powder; S2: The obtained ZIF-67@PDA powder is heat-treated to obtain a dopamine-coated Co organic framework hollow dodecahedron; S3: adding a variety of soluble metal salt solutions and molten salts to the reaction system obtained in step S2, freeze-drying after ultrasonic treatment, and pyrolyzing under a nitrogen atmosphere; S4: Wash with acid solution and deionized water to remove the salt template and aggregated metal particles to obtain a high-entropy single-atom catalyst supported on ultrathin carbon nanosheets.

2. The method for preparing a high-entropy single-atom catalyst supported by molten salt-assisted synthesis of ultra-thin carbon nanosheets according to claim 1, characterized in that: In step S1, the nitrogen source in the dopamine solution includes one or more of dopamine, urea, melamine and glycine.

3. The method for preparing a high-entropy single-atom catalyst supported by molten salt-assisted synthesis of ultra-thin carbon nanosheets according to claim 2, characterized in that: In step S1, the pH value of the tris(hydroxymethyl)aminomethane hydrochloride) buffer solution is 7-9.

4. The method for preparing a high-entropy single-atom catalyst supported by molten salt-assisted synthesis of ultra-thin carbon nanosheets according to claim 3, characterized in that: In step S1, the mass volume ratio of the ZIF-67 powder to the tris(hydroxymethyl)aminomethane hydrochloride buffer solution is (0.1-0.2) g: (60-80) ml.

5. The method for preparing high-entropy single-atom catalyst supported by molten salt-assisted synthesis of ultra-thin carbon nanosheets according to claim 4, characterized in that: In step S3, the metal elements in the soluble metal salt solution are selected from at least four of Fe, Ni, Ir, Pd, and Ce, and the soluble metal salt solution is selected from at least one of nitrate, chloride, acetylacetonate, and acetate; The molten salt includes at least one or more of sodium chloride, calcium chloride and potassium chloride.

6. The method for preparing high-entropy single-atom catalyst supported by molten salt-assisted synthesis of ultra-thin carbon nanosheets according to claim 5, characterized in that: In step S3, the mass ratio of the dopamine-coated cobalt metal organic framework hollow dodecahedron to the soluble metal salt solution is 2:5; The mass ratio of the soluble metal salt to the molten salt is 1:

3.

7. The method for preparing high-entropy single-atom catalyst supported by molten salt-assisted synthesis of ultra-thin carbon nanosheets according to claim 1, characterized in that: In step S3, the pyrolysis temperature in the nitrogen atmosphere is 600-800°C, the time is 1-3h, and the heating rate is 1°C / min-10°C / min.

8. A molten salt-assisted synthesis of ultrathin carbon nanosheets loaded with high entropy single-atom catalysts, characterized in that: The method for preparing a high-entropy single-atom catalyst supported on ultra-thin carbon nanosheets by molten salt-assisted synthesis is adopted as described in any one of claims 1 to 7.

9. The molten salt-assisted synthesis of ultra-thin carbon nanosheets supported high entropy single-atom catalyst according to claim 8, characterized in that: The ultra-thin carbon nanosheet-loaded high-entropy single-atom catalyst includes metal elements Fe, Co, Ni, Ir, and Pd; and the atomic molar ratio of Fe, Co, Ni, Ir, and Pd is 0.8:1:0.8:0.6:0.4; Alternatively, the ultrathin carbon nanosheet-supported high-entropy single-atom catalyst includes metal elements Fe, Co, Ni, Ir, and Ce, and the atomic molar ratio of Fe, Co, Ni, Ir, and Ce is 0.7:1:0.6:0.6:0.4; Alternatively, the ultra-thin carbon nanosheet-supported high-entropy single-atom catalyst includes metal elements Fe, Co, Ni, Pd, and Ce, and the atomic molar ratio of Fe, Co, Ni, Pd, and Ce is 0.7:1:0.6:0.5:0.5; The ultra-thin carbon nanosheet has a thickness of 0.4 to 1.2 nm.

10. Use of the molten salt-assisted synthesis of ultra-thin carbon nanosheets loaded with high entropy single-atom catalysts as described in claim 8 or 9 in positive electrode sheets, secondary batteries, electrocatalytic materials, lithium-sulfur batteries and lithium metal batteries.

Citation Information

Patent Citations

  • Method for preparing carbon carrier and synthesizing Pt-Sn catalyst by calcining ZIF-8 molten salt

    CN113745553A

  • Carbon-coated cobalt-copper bimetallic phosphide composite nanomaterial and preparation method and application thereof

    CN117954613A

  • Manufacturing method based on simultaneous encapsulation of target substance and synthesis of mofs having redox activity

    WO2018045824A1

  • Synthesis method and synthesis device for organic nitrogen-containing compound

    WO2023198025A1